Fretting wear of lubricated DLC coating systems - McMaster, Samuel J.; Kosarieh, Shahriar; Liskiewicz, Tomasz W.; Beake, Ben D. (Frontiers in Mechanical Engineering, 2025)
Diamond-like Carbon (DLC) coatings are well known for their use in protection against fretting wear due to their low friction and wear properties. DLCs are metastable, allowing them to graphitise under applied load to create a graphitic transfer layer which reduces friction. Their high intrinsic residual stresses also enable them to resist cracking effectively under fretting. Few studies have analysed the lubricated fretting performance of DLC coating systems. This work focuses on a series of lubricants with different additives and friction modifiers to explore their effects. This study analyses the performance of a DLC coating system (a-C:H) applied to hardened M2 tool steel and 316L stainless steel under loads of 20 and 40 N under dry fretting and lubricated fretting conditions. Lubricated uncoated substrates were also analysed for comparison. The counterfaces used were 10 mm diameter 52,100 steel balls. The lubricants tested included a base oil and a fully formulated oil, with and without the addition of MoDTC. Gross slip fretting was achieved using a bespoke electrodynamic shaker unit. Nanoindentation was employed to measure the mechanical properties of the coatings and substrates. Contact pressure and lubricant type had significant effects on the running-in behaviour of the coatings. Increased contact pressure led to instability in the running-in period. Lubrication reduced the dissipated energy in the contact, thereby decreasing wear. However, fully formulated oils and those containing MoDTC performed worse due to their higher viscosity, which impacted oil entrainment in the contact area. This study provides insights into the lubricated fretting performance of DLC coatings showing that these coatings can perform well, with the potential for further improvements with optimisations to the lubricant to the system. Performance improvements can be gained in automotive components such as high pressure bearings and gears.